2012
DOI: 10.1007/s10584-012-0479-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of reference evapotranspiration and its contributing climatic factors in Yunnan Province, SW China, 1961–2004

Abstract: Questions: Density-dependent processes may promote species diversity in plant communities. Here, we tested whether seedling survival was density-dependent and varied by seedling size, species and climatic factors. Location: Tropical rain forest, Xishuangbanna, southwest China. Methods: Generalized linear mixed-effects models were used to examine seedling survival (232 tree species) across 9 years of seedling census data from a 20-ha tropical forest dynamics plot. Our predictor variables were conspecific and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 73 publications
11
62
0
Order By: Relevance
“…During the study period, the observed variations in Max T, Min T, and Ave T were similar to the global pattern of increasing minimum, mean, and maximum temperature [12]; and the results of the analysis of other climatic factors were consistent with the findings reported from Yunnan Province in southwest China during 1961-2004 [5]. There, the sensitivity analyses for changes in the annual ET 0 showed that Ave RH and Max T were the most sensitive climate variables over the whole Songnen Grassland, which was in agreement with Yin et al [44], who studied all of China during 1961-2008.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…During the study period, the observed variations in Max T, Min T, and Ave T were similar to the global pattern of increasing minimum, mean, and maximum temperature [12]; and the results of the analysis of other climatic factors were consistent with the findings reported from Yunnan Province in southwest China during 1961-2004 [5]. There, the sensitivity analyses for changes in the annual ET 0 showed that Ave RH and Max T were the most sensitive climate variables over the whole Songnen Grassland, which was in agreement with Yin et al [44], who studied all of China during 1961-2008.…”
Section: Discussionsupporting
confidence: 88%
“…They are all distributed inside or adjacent to the study area in order to cover the entire region. All selected stations have good-quality data and meet the QA (Quality assurance)/QC (Quality control) requirements, which means that the spatial distribution of the stations had to cover the entire region, the time series had to be long enough to obtain statistically significant results in trend analyses, and the climate data was The FAO-56 Penman-Monteith (FAO-PM) equation was recommended as the sole and global standard method for ET 0 calculation [5,20]. The method has been widely verified for its accuracy and reliability in various climatologic zones around the world [21,22].…”
Section: Climate Data and Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The most influential factor in the changes of ETo was decreased R s in summer and growing season (Fig. 6b, e), the same as studies in Yunnan province of southwestern China (Fan and Thomas, 2012), subtropical and tropical regions in…”
Section: Contributions Of Meteorological Variables To Eto Trendssupporting
confidence: 79%
“…Although the annual rainfall and temperature of the Satkhira station exhibited positive trends (Kamruzzaman et al, 2016a), its P ET exhibited a significant decreasing trend. Increasing temperature and decreasing P ET trends were observed in the Yunnan Province of South China (Fan and Thomas, 2012). McVicar et al (2012) also found decreasing P ET trends in different parts of the world.…”
Section: Discussionmentioning
confidence: 82%